Gastronomic Metaphor in the Russian Pre-Revolutionary Parliamentary Discourse (based on Speeches by Right-Wing Deputies) - S. A. Gromyko (Научный диалог, 2020)
The results of a study of the semantics and functioning of the gastronomic metaphor in the Russian parliamentary discourse are presented in the article. Based on the material of the parliamentary discussion of the early twentieth century, the features of the functioning of metaphors, which are based on the associative similarity between political activity and food, the eating process are established. The author dwells in detail on the use of gastronomic metaphors by nationalist deputies in the course of discussions unfolding at meetings of the State Duma. The results of the classification of metaphors identified on the indicated material belonging to the “Food” sphere are presented. It was established that they can be divided into three groups according to the figurative component: metaphors with the literal meaning of absorbing or eating something, metaphors with the value of the quality of food consumed, metaphors with the value of the digestion process. It is concluded that in the semantic aspect, the gastronomic metaphor in the Russian parliamentary discourse expresses a persistent negative assessment, since it is associated with the semantics of extermination, destruction, deception ( to give a stone instead of bread ), abnormal physiological phenomena (hunger, overeating, indigestion). It is emphasized that in the functional aspect, the negative appraisal of the gastronomic metaphor made it possible to use it in parliamentary discourse as a means of political struggle with the aim of lowering the political assets of opponents.